EFFICACY OF LAPAROSCOPIC LONGITUDINAL GASTRECTOMY FOR CORRECTION OF OBSTRUCTIVE SLEEP APNEA SYNDROME IN PATIENTS WITH MORBID OBESITY - Alijon S. Murodov; Oktyabr R. Teshaev; Alimbay Mavlanev (Central Asian Journal of Medicine, 2023)
Studying the effectiveness of longitudinal gastrectomy on obstructive sleep apnea syndrome in patients with morbid obesity(MO). This scientific work is based on the results of a comprehensive examination and treatment of 187 patients with MO who were treated in the our clinical bases from 2021 to 2023. The analysis of comorbidities in the compared groups showed that one or more comorbidities were detected in 52% of the control group, 57.5% of the main group, and 22.2% of the patients in the main group had sleep apnea syndrome. The main part of these patients was made up of patients with obesity of the III degree We studied BMI, waist and neck circumference in patients with morbid obesity after laparoscopic longitudinal gastrectomy. Three months after laparoscopic longitudinal gastrectomy, patients’ BMI decreased significantly by 21.0 ± 2.5%, as well as waist circumference by 14.0 ± 1.9%. Also, a significant decrease in neck circumference was found after the surgery, which was 12.0±2.5%. These indicators show that after longitudinal gastric resection in patients with morbid obesity, the above indicators, corresponding to the patient’s body weight and BMI improved, leading to a significant reduction in the symptoms of obstructive sleep apnea syndrome in patients.